2011
DOI: 10.1007/s00467-010-1695-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic susceptibility to renal scar formation after urinary tract infection: a systematic review and meta-analysis of candidate gene polymorphisms

Abstract: Identifying patients who may develop renal scarring after urinary tract infections (UTI) remains challenging, as clinical determinants explain only a portion of individual risk. An additional factor that likely affects risk is individual genetic variability. We searched for peer-reviewed articles from 1980 to December 2009 in electronic databases that reported results showing an association between gene polymorphims and renal scaring after UTI. Two independent researchers screened articles using predetermined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 58 publications
0
28
0
1
Order By: Relevance
“…All VUR children were excluded from this study. Our rationale was that we needed to study the effect of the genetic predisposition on the susceptibility to renal parenchymal infection without the confounding effect of VUR, which is an established risk factor for APN .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All VUR children were excluded from this study. Our rationale was that we needed to study the effect of the genetic predisposition on the susceptibility to renal parenchymal infection without the confounding effect of VUR, which is an established risk factor for APN .…”
Section: Resultsmentioning
confidence: 99%
“…While UTIs present clinically as asymptomatic bacteriuria, cystitis and acute pyelonephritis (APN), lower UTIs may progress to APN with the risk of developing renal parenchymal scarring (RPS), hypertension and eventually deterioration of renal function . The question about why some children develop lower UTIs and others develop APN, despite having an anatomically normal urinary tract, still poses a research dilemma and has raised the possibility of genetic predisposition . Identifying the possible role of genetic variants in APN would help the clinicians to recognise which children are at greater risk based on their genetics.…”
Section: Introductionmentioning
confidence: 99%
“…Although we have not analyzed genetic susceptibility as the risk factor for ASL and USF several reports demonstrated the role of genetic susceptibilities as clinical determinants explain only a portion of individual risk [25]. Meta-analysis by Zaffanello et al revealed association between renal scarring formation after UTI and angiotensin enzyme insertion/deletion polymorphism or transforming growth factor-beta 1 c.509 T>C polymorphism [3,9,25].…”
Section: Discussionmentioning
confidence: 96%
“…Polymorphisms of genes regulating different stages of the inflammatory process, from the initial inflammation to fibrosis, have been associated with UTI-related renal scarring (22,23). Polymorphisms of genes regulating different stages of the inflammatory process, from the initial inflammation to fibrosis, have been associated with UTI-related renal scarring (22,23).…”
Section: Discussionmentioning
confidence: 99%